2020
DOI: 10.3389/fneur.2020.00805
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Neurology Consultations During the Onset of the SARS-CoV-2 New York City Pandemic: A Single Center Case Series

Abstract: Objective: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) primarily causes respiratory illness. However, neurological sequelae from novel coronavirus disease 2019 (COVID-19) can occur. Patients with neurological conditions may be at higher risk of developing worsening of their underlying problem. Here we document our initial experiences as neurologic consultants at a single center quaternary hospital at the epicenter of the COVID-19 pandemic. Methods: This was a retrospective case series of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Finally, the other studies identified in our review concerned COVID‐19 in adults 12,17,20 . Radmard et al 21 discussed neurological complications after COVID‐19 and presented data on 33 patients. There was only one paediatric patient under the age of 18 and that individual was 17 years of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the other studies identified in our review concerned COVID‐19 in adults 12,17,20 . Radmard et al 21 discussed neurological complications after COVID‐19 and presented data on 33 patients. There was only one paediatric patient under the age of 18 and that individual was 17 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…The author read 19 in detail after screening the titles and abstracts. Of these, 11 were from MEDLINE, [10][11][12][13][14][15][16][17][18][19][20] two from EMBASE, 21,22 five from Web of Science [23][24][25][26][27] and one from medRxiv/bioRxiv. 28 There was no pre-specified protocol prior to the review.…”
Section: Systematic Literature Searchmentioning
confidence: 99%
“…The development of an epilepsy electronic patient portal may promote improved patient-clinician partnerships and facilitate patient self-management [23] 1.2. Seizure-related papers (Table 3): While one retrospective study reported no seizures in 304 patients with COVID-19 [25], multiple studies refuted that finding [24,[26][27][28][29]. Furthermore, many cases with new-onset focal seizures, serial seizures, and status epilepticus have been reported in the literature [30-49, 51, 63].…”
Section: Resultsmentioning
confidence: 99%
“…Another important issue is the occurrence of new-onset seizures in people with COVID-19. While seizure is not a common manifestation of COVID-19, it may happen in a variety of forms (e.g., focal motor, tonic-clonic, convulsive status epilepticus, and nonconvulsive status epilepticus) [28,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. On the other hand, many patients with severe COVID-19 may have changes in their mental status [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COVID-19, particularly those with severe disease, experience neurologic manifestations with symptoms such as dizziness, headache, seizures, impaired consciousness, and acute cerebrovascular disease [ 12 , 75 , 76 ]. Central nervous system (CNS) complications are reported to manifest early in the course of infection [ 12 ].…”
Section: Main Textmentioning
confidence: 99%